Strategy for building customer loyalty amidst shifting consumer behavior: Mediating role of purchase intention - Wijayanti, Novi; Wagiyem, Wagiyem (Trigin Publisher, 2025)
This quantitative study investigates the factors influencing the brand awarness, brand association, brand image on customer loyalty trought purchase intention, employing a survey of 150 buyer of Uniqlo product. Using structural equation modeling, we examined the relationships between construct with mediation role. This study reveals that while brand association and brand image significantly influence purchase intention, brand awareness does not. Furthermore, brand awareness and brand image directly impact customer loyalty, whereas brand association does not exhibit a significant direct effect. Notably, purchase intention fully mediates the relationship between brand association and customer loyalty, and partially mediates the impact of brand image on customer loyalty, but does not mediate the relationship between brand awareness and customer loyalty. Organizations should strategically prioritize enhancing brand association and image to drive purchase intention and cultivate customer loyalty, while recognizing that brand awareness alone may not directly translate to immediate purchase decisions or loyalty. Future research could explore the nuanced mechanisms through which specific dimensions of brand awareness indirectly influence loyalty, potentially through other mediating factors beyond purchase intention, or investigate the moderating roles of consumer characteristics and contextual factors in these relationships.